Chemical composition of DNA-encoded libraries, past present and future. Issue 19 (24th April 2019) - Dickson, Paige; Kodadek, Thomas
Abstract : We discuss here the chemical composition of DNA-encoded libraries likely to be made in the near future. Abstract : DNA-encoded libraries represent an exciting and powerful modality for high-throughput screening. In this article, we highlight recent important advances in this field and also suggest some important directions that would make the technology even more powerful.